Synthesis and Characterization of Anatase TiO2:Cu2+ Powders Prepared via a Sol-gel Technique - Loan, Trinh Thi; Ngoc Long, Nguyen (VNU Journal of Science: Mathematics - Physics, 2018)
Anatase TiO 2 powders doped with different amounts of Cu 2+ ions (0, 0.5, 1.0 and 4 mol%) were successfully synthesized by sol-gel method from precursors of TiCl 4 , (CH 3 COO) 2 Cu. Effect of Cu 2+ concentrations on the structural and optical properties of TiO 2 host was investigated by X-ray diffraction, Raman spectroscopy and diﬀuse reﬂection spectroscopy. The XRD analysis showed that the doped samples exhibit anatase single phase at annealing temperature 600 o C.  The Cu 2+ contents did not affect on the lattice of TiO 2 hot, but affected on positions of these Raman modes. The band gap of the TiO 2 :Cu 2+ was decreased with the increase of doping concentration.